2017
DOI: 10.1007/s10439-017-1906-5
|View full text |Cite
|
Sign up to set email alerts
|

Review of Mechanical Testing and Modelling of Thrombus Material for Vascular Implant and Device Design

Abstract: A thrombus or blood clot is a solid mass, made up of a network of fibrin, platelets and other blood components. Blood clots can form through various pathways, for example as a result of exposed tissue factor from vascular injury, as a result of low flow/stasis, or in very high shear flow conditions. Embolization of cardiac or vascular originating blood clots, causing an occlusion of the neurovasculature, is the major cause of stroke and accounts for 85% of all stroke. With mechanical thrombectomy emerging as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 55 publications
0
30
0
Order By: Relevance
“…Additionally, thrombus testing methods have varied, employing uniaxial tensile and compressive testing, planar biaxial testing, nanoindendation, small and large angle shear rheometry, and now simple shear (this publication). For a comprehensive review of the thrombus mechanics literature please see Johnson et al and the works cited therein (Johnson et al, 2017). Interestingly, van Oosten et al have argued that it is the densely-packed cellular ele-ments in thrombus that may render it non-shear stiffening.…”
Section: Mechanics Of Our Thrombus Mimicmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, thrombus testing methods have varied, employing uniaxial tensile and compressive testing, planar biaxial testing, nanoindendation, small and large angle shear rheometry, and now simple shear (this publication). For a comprehensive review of the thrombus mechanics literature please see Johnson et al and the works cited therein (Johnson et al, 2017). Interestingly, van Oosten et al have argued that it is the densely-packed cellular ele-ments in thrombus that may render it non-shear stiffening.…”
Section: Mechanics Of Our Thrombus Mimicmentioning
confidence: 99%
“…The latter outcome is the most catastrophic leading to approximately 100,000 deaths every year in the US alone according to the CDC (Beckman et al, 2010). The deformation, fracture, and eventual embolization of thrombus are inherently mechanical processes (Basmadjian, 1989;Johnson et al, 2017). Thus, the mechanics of thrombus, and venous thrombus in particular, has been of immense interest.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of red blood cells gives rise to a white thrombus that is stiffer and possesses a higher coefficient of friction than red thrombi. 6,7 Shear Exposure Depends on Mitral MHV Design and Orientation Previous studies have found the mitral inflow jet is altered for MHV recipients and is highly dependent on the geometry of the prosthesis. 8,9 In the authors' laboratory, the velocity field of a dilated left ventricle (LV) model was measured in a mock cardiovascular loop for different mitral prostheses and used to characterize the blood residence time (TR) and platelet shear activation potential (SAP) based on the cumulative exposure to shear.…”
Section: Thrombus Formation Is Dependent On Shear Exposurementioning
confidence: 99%
“…The spontaneous embolism of a thrombus especially in acute coronary events may be a natural protective mechanism against infarction in organs [43] . Past studies have focused on individual platelet behaviour and more recently, there has been new interest in investigating factors related to thrombus stability that are able to be correlated with acute coronary events.…”
Section:  Quantifying Embolismmentioning
confidence: 99%